2009
DOI: 10.1111/j.1540-5850.2009.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Budgeting in Midwestern States: Democratic Connection or Citizen Disconnection?

Abstract: What participation mechanisms connect citizens and city officials? Do they produce valued outcomes? Surveys of elected officials suggest that microlevel mechanisms such as direct citizen contact are more valuable in meeting participation goals than are mechanisms focusing on macrolevel concerns. However, there is a disconnect between perceptions about value and the use of mechanisms. State-level participation requirements and a city manager have little effect on the value of a mechanism. These findings raise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 2 publications
1
66
0
1
Order By: Relevance
“…From this standpoint, advocates maintain that the responsiveness of governments enhances governmental accountability and the effectiveness of performance measurements. Citizen feedback on governmental services and programs has been incorporated into performance measurements to more accurately represent citizen needs in policy decisions (A. L. Franklin, Ho, & Ebdon, 2009;Wichowsky & Moynihan, 2008). Various ways --such as voting, campaigning, joining an interest group, relying on citizen surveys, using citizen advisory committees, and attending public hearings --have been used to increase government responsiveness in performance management (Franklin et al, 2009;Swindell & Kelly, 2000).…”
Section: B Significance Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…From this standpoint, advocates maintain that the responsiveness of governments enhances governmental accountability and the effectiveness of performance measurements. Citizen feedback on governmental services and programs has been incorporated into performance measurements to more accurately represent citizen needs in policy decisions (A. L. Franklin, Ho, & Ebdon, 2009;Wichowsky & Moynihan, 2008). Various ways --such as voting, campaigning, joining an interest group, relying on citizen surveys, using citizen advisory committees, and attending public hearings --have been used to increase government responsiveness in performance management (Franklin et al, 2009;Swindell & Kelly, 2000).…”
Section: B Significance Of the Studymentioning
confidence: 99%
“…Citizen feedback on governmental services and programs has been incorporated into performance measurements to more accurately represent citizen needs in policy decisions (A. L. Franklin, Ho, & Ebdon, 2009;Wichowsky & Moynihan, 2008). Various ways --such as voting, campaigning, joining an interest group, relying on citizen surveys, using citizen advisory committees, and attending public hearings --have been used to increase government responsiveness in performance management (Franklin et al, 2009;Swindell & Kelly, 2000). By focusing on QoL, this study contributes to fuller understanding of public performance management, to probing the linkage of policy choices and citizen needs, to furthering a normative standard for reducing social inequality, and to examining more fully the potential influences on local policy decisions.…”
Section: B Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been illustrated by the results of research conducted by scholars such as Franklin et al [3], Davenport and Skandera [1], Vissanu and Salahudin (2016), Souza [11], and King et al [9]. They have indicated that local government has dominated civic groups in the budgetary process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the final approved budget may be seen as taking the side of the administrators of public affairs. As highlighted by Franklin et al [3], budget planning is underlined by the actions of administration officials. This causes a disproportionate distribution in favor of government over social affairs in budget policy [15].…”
Section: Introductionmentioning
confidence: 99%